Real-Life Problems to Increase the Critical Analysis Thinking Among Novice Counselors in Humanistic Counseling Courses: Is It Effective? - Irani, Luthfita Cahya; Suwarjo, Suwarjo; Nhung, Le Ngoc Ai (Jurnal Kajian Bimbingan dan Konseling, 2022)
This study aims to determine the effectiveness of using real-life problems to improve novice counsellors' critical analytical thinking in humanistic counselling courses. The research method uses an experiment with a pretest-posttest control group design. The instrument used is a critical-analytical thinking scale. The research sample used a purposive sampling technique, which consisted of 84 students of the 2018 Guidance and Counseling UNY Study Program who took the Humanistic Counseling course. The samples were separated into experimental and control groups of 42 students. The pre-test and post-test data were analyzed using an independent sample t-test using SPSS Amos 25 software. The results show that the use of real-life problems in the Humanistic Counseling course was proven effective in improving students' critical-analytical thinking as novice counsellors. As a result, students are more stimulated to practice analyzing cases in various ways and can activate their cognitive complexity processes as novice counsellors.